PERTANGGUNGJAWABAN PERDATA KEPOLISIAN TERHADAP KORBAN SALAH TEMBAK DI WILAYAH HUKUM POLRESTA PASAMAN BARAT - Yevendri, Zulkhairi dan (Fakultas Hukum Universitas Tamansiswa Padang, 2021)
The police's civil responsibility for the victims of a wrong shot in the West Pasaman Police area based on Decision No. 04/Pdt.G/2007/Pn.Psb is liability based on a fault (fault of liability). For this mistake, the Indonesian National Police are required to provide compensation arising from unlawful acts committed by Brigadier Nofrizal, as well as being sentenced to pay compensation (immaterial) to the Plaintiff in the amount of Rp. 300,000,000, - (three hundred million rupiah). The judge's consideration in making a decision in asking the police for civil liability for the plaintiff's shooting mistake in the West Pasaman Police area based on Decision No. 04/Pdt.G/2007/Pn.Psb is based on the provisions of Article 1365 and Article 1367 of the Civil Code, which are based on the elements: the existence of an act, the act is against the law, the loss to the victim, the fault of the perpetrator, the existence of causality between action and loss.